A facile immersion-curing approach to surface-tailored poly(vinyl alcohol)/silica underwater superoleophobic coatings with improved transparency and robustness. Issue 22 (10th April 2017) - Gu, Yunjiao; Yang, Jiahua; Zhou, Shuxue
Abstract : Robust and transparent superhydrophilic/underwater-superoleophobic self-cleaning composite coatings with hierarchical surfaces can be realized with low filler contents simply through immersion-curing. Abstract : Oil contamination is problematic in subaqueous environments. It is difficult to prepare long-lasting textured superhydrophilic/underwater oil-repellent coatings without using a sophisticated method. Here, an ultra-facile and low-cost immersion-curing approach has been developed to generate superhydrophilic and underwater superoleophobic coatings from poly(vinyl alcohol) (PVA)/silica (SiO2 ) nanocomposites. During immersion curing, polymeric dissolution occurs simultaneously with crosslinking but occurs solely at the topmost layer, and helps to create enriched hierarchical surface micro-/nanostructures. Hence, superhydrophilicity is attainable for nanocomposite coatings with a filler percentage of only 15 wt%. Immersion-cured PVA/SiO2 nanocomposite coatings with 35 wt% silica have an excellent underwater superoleophobicity in terms of durability and ultra-low oil adhesion towards a variety of oils, including viscous crude oil. Because of its lower filler content and confined porous structure, this coating has a greater transparency compared with its conventional blend-curing underwater superoleophobic counterpart. Immersion-cured nanocomposite coatings display an excellent mechanical durability based on pencil hardness (3H) and sand-abrasion performance. The extra acrylic/melamine base-coat allows the underwater superoleophobic PVA/SiO2 coatings to be applied to diverse substrates, including glass, metals, and plastics, and renders them free from oil in aqueous environments.